2010
DOI: 10.3109/09638280903437253
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and validity of the Motor Activity Log in patients during the subacute phase after stroke

Abstract: The MAL is a responsive measure of daily hand use in patients participating in rehabilitation in the subacute phase after stroke. Correlations of construct validity indicate that daily hand use may need to be measured separately from body function and activity capacity, in line with the underlying constructs of International Classification of Functioning, Disability and Health. To strengthen our findings, they should be repeated in larger samples of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
(65 reference statements)
2
35
0
1
Order By: Relevance
“…The use of a measure of precise movement of the digits during recovery, such as the Grasp Assessment Scale adapted for this study, not only to provide an in-depth analysis of the nature of the compensatory movement but also because quantitative measures of performance alone (e.g., latency to retrieve or number of pellets retrieved) could fail to detect the development of compensatory movements and may lead to the incorrect conclusion about the nature of recovery. This issue has also been raised in several clinical studies assessing the efficacy of tests of arm function (Hammer and Lindmark, 2010; Heller et al, 1987; Lum et al, 2009; Sunderland et al, 1999; Wade, 1989). It has been suggested that many clinical assessments of arm function provide a pass/fail or a latency score but not a detailed assessment of the nature of upper extremity movements and that future studies should include more detailed analysis of these movements (Raghavan et al, 2010; Saver, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a measure of precise movement of the digits during recovery, such as the Grasp Assessment Scale adapted for this study, not only to provide an in-depth analysis of the nature of the compensatory movement but also because quantitative measures of performance alone (e.g., latency to retrieve or number of pellets retrieved) could fail to detect the development of compensatory movements and may lead to the incorrect conclusion about the nature of recovery. This issue has also been raised in several clinical studies assessing the efficacy of tests of arm function (Hammer and Lindmark, 2010; Heller et al, 1987; Lum et al, 2009; Sunderland et al, 1999; Wade, 1989). It has been suggested that many clinical assessments of arm function provide a pass/fail or a latency score but not a detailed assessment of the nature of upper extremity movements and that future studies should include more detailed analysis of these movements (Raghavan et al, 2010; Saver, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The average time (WMFT-Time) and functional ability scores (WMFT-FAS) of the paretic arm were reported. Activities of daily living were measured with the Motor Activity Log (MAL) [45] and the ABILHAND Questionnaire [46]. The MAL is a reliable and valid 30-item measure of how patients perceive the use of their paretic UE during real-world activities.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] The MAL is a semistructured interview that obtains information about how participants use their affected limbs during 30 important daily activities and assesses the AOU and the quality of movement (QOM) of the affected arm. [24][25][26][27] …”
Section: Secondary Outcome Measures: Clinical Measuresmentioning
confidence: 98%